STUDY OF NATURAL BEE HONEY PRODUCTION FROM THE BUKIT GATAN PROTECTED FOREST AREA, SOUTH SUMATERA PROVINCE (Sylva : Jurnal Penelitian Ilmu-Ilmu Kehutanan, 2022)
This research was conducted to determine the types of bees produced, the amount of production produced in each colony, branches, trees, and the total production produced by honey bees, as well as the harvesting, processing, and marketing production processes carried out. The research method used is a survey, while the sampling method used is a combination of purposive sampling and snowball sampling. The data collection method used in this study was direct observation and interviews with informants using a list of questions. Data analysis was carried out descriptively quantitatively. Furthermore, the amount of production is calculated by the census. The results showed that the type of bee produced was Apis dorsata, the amount of honey produced in each colony was 8.4 kg/year on average, each branch had a colony with an average of 1.82 colonies/branch, and each tree had an average number of an average of 10.3 colonies/tree. The amount of honey production per harvest in August is an average of 44.3kg/month and in September is an average of 43kg/month with an average total production of 87.3kg/year and the harvesting production process consists of preparing tools, installing ladders, climbing , fumigating, slicing the nest and lowering the nest, then the honey processing production process consists of filtering and packaging honey, and the marketing production process is carried out by promoting honey through communication between consumers.